Unusual (CGG)n expansion and recombination in a family with fragile X and DiGeorge syndrome. Issue 3 (March 1995) - Macpherson, J N; Curtis, G; Crolla, J A; Dennis, N; Migeon, B; Grewal, P K; Hirst, M C; Davies, K E; Jacobs, P A
Abstract : In a fragile X family referred for prenatal diagnosis, the female fetus did not inherit the full fragile X mutation from her mother, but an unexpected expansion within the normal range of CGG repeats from 29 to 39 was observed in the paternal X chromosome. Also, a rare recombination between DXS548 and FRAXAC1 was recorded in the maternal meiosis. Follow up of the neonate confirmed the same DNA genotype as in the CVS, but the child died of DiGeorge syndrome after four days and was subsequently found to carry a microdeletion of chromosome 22 using probe cEO. It is suggested that in this family the deletion of chromosome 22 is likely to be a chance event but the rare recombinant and the fragile X mutation might be causally related.